Biased attention to threat and anxiety: On taking a developmental approach. Issue 3 (19th August 2019) - Burris, Jessica L.; Buss, Kristin; LoBue, Vanessa; Pérez-Edgar, Koraly; Field, Andy P.
Several researchers have proposed a causal relation between biased attention to threat and the development and maintenance of anxiety disorders in both children and adults. However, despite the widely documented correlation between attention bias to threat and anxiety, developmental research in this domain is limited. In this review, we highlight the importance of taking a developmental approach to studying attention biases to threat and anxiety. First, we discuss how recent developmental work on attention to threat fits into existing theoretical frameworks for the development of anxiety and how attention biases might interact with other risk factors across development. Then we review the developmental literature on attention bias to threat and anxiety and describe how classic methodologies can be modified to study attention biases in even the youngest infants. Finally, we discuss limitations and future directions in this domain, emphasizing the need for future longitudinal research beginning in early infancy that tracks concurrent developments in both biased attention and anxiety. Altogether, we hope that by highlighting the importance of development in the study of attention bias to threat and anxiety, we can provide a road map for how researchers might implement developmental approaches to studying a potential core mechanism in anxiety.